Effect of composition on the structure of lithium- and manganese-rich transition metal oxides. Issue 4 (19th January 2018) - Shukla, Alpesh Khushalchand; Ramasse, Quentin M.; Ophus, Colin; Kepaptsoglou, Despoina Maria; Hage, Fredrik S.; Gammer, Christoph; Bowling, Charles; Gallegos, Pedro Alejandro Hernández; Venkatachalam, Subramanian
Abstract : In this work, we establish a definitive structural model for lithium- and manganese-rich transition metal oxides and demonstrate the effect of composition on their bulk as well as the surface structure. Abstract : The choice of chemical composition of lithium- and manganese-rich transition metal oxides used as cathode materials in lithium-ion batteries can significantly impact their long-term viability as storage solutions for clean energy automotive applications. Their structure has been widely debated: conflicting conclusions drawn from individual studies often considering different compositions have made it challenging to reach a consensus and inform future research. Here, complementary electron microscopy techniques over a wide range of length scales reveal the effect of lithium-to-transition metal-ratio on the surface and bulk structure of these materials. We found that decreasing the lithium-to-transition metal-ratio resulted in a significant change in terms of order and atomic-level local composition in the bulk of these cathode materials. However, throughout the composition range studied, the materials consisted solely of a monoclinic phase, with lower lithium content materials showing more chemical ordering defects. In contrast, the spinel-structured surface present on specific crystallographic facets exhibited no noticeable structural change when varying the ratio of lithium to transition metal. The structural observations from this study warrant a reexamination of commonly assumed models linking poor electrochemical performance with bulk and surface structure.